The determinants of arab economic development - Sayigh, Yusif A. (London Croom Helm, 1978)
This book explores in depth the factors determining economic development in the Arab region. The particular factors relevant to the Arab world are also set within the context of the broad political economy of underdevelopment. The factors are identified as comprising three main groups: economic, political administrative and socio-cultural; petroleum and regional Arab economic development are examined separately. The force and operation of each determinant is further assessed in the context of the individual countries, from which the author is able to arrive at some important conclusions concerning the interaction of these determinants and their impact upon development (From Amazon page)
​Acknowledgements -- 1. Development and its determinants: some conceptual and methodological issues -- 2. The determinants in operation -- 3. The outlook for development -- Index
This edition was first published in 2015 by Routledge
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC CONDITIONS; ARAB COUNTRIES